Pediatric Radiation Dose from 64 Slices-MDCT in Abdomen after Using the New Pediatric CT Scanning Protocol at Phramongkutklao Hospital - Khampunnip, Suvicha; Khampunnip, Sutiporn; Sutthipong, Kaywalin; Saengruang-orn, Supakajee (The Bangkok Medical Journal, 2020)
OBJECTIVES: To study the radiation dose in pediatric patients after using a new pediatric computed tomography (CT) scanning protocol at Phramongkutklao Hospital as compared with the historical data and with reference level recommended by International Commission on Radiological Protection (ICRP). MATERIALS AND METHODS: This study was a prospective and descriptive study. The study target population were all consecutive patients aged <15 year-old who had received a 64-slice computed tomography of the abdomen from January 2015- August 2016 using the new protocol. The control group was patients in the same age group performing CT scan of abdomen in the past before using the new protocol. RESULTS: Total of 29 children were included in the analysis, 13 were male and 16 were female. The third quartile of the dose-length product (DLP) (75th percentile) was 125.0, 228.0, 305.6 and 381.0 mGy.cm for the patients < 1, 1 to < 5, 5 to < 10 and 10 to <15 year-old respectively. These DLP values were significantly lowered than previously reported in Thailand in almost patient age groups. CONCLUSION: The radiation dose that our pediatric patients received from undergoing CT scan of abdomen was acceptable after using the new protocol. Data collection in future studies including a higher number of patients and longer follow-up time may be helpful.